Leishmania Major Centrin Gene-Deleted Parasites Generate Skin Resident Memory T-Cell Immune Response Analogous to Leishmanization - Ismail, Nevien; Karmakar, Subir; Bhattacharya, Parna; Sepahpour, Telly; Takeda, Kazuyo; Hamano, Shinjiro; Matlashewski, Greg; Satoskar, Abhay R.; Gannavaram, Sreenivas; Dey, Ranadhir; Nakhasi, Hira L. (Frontiers in Immunology, 2022)
Leishmaniasis is a vector-borne parasitic disease transmitted through the bite of a sand fly with no available vaccine for humans. Recently, we have developed a live attenuated Leishmania major centrin gene deleted parasite strain (LmCen-/-) that induced protection against a homologous and heterologous challenges. We demonstrated that the protection is mediated by IFN secreting CD4+ T effector cells and multifunctional T cells, which is analogous to leishmanization. In addition, in a leishmanization model skin tissue resident memory T cells (TRM cells) were also shown to be crucial for host protection. In this study, we evaluated generation and function of skin TRM cells following immunization with LmCen-/- parasites and compared those with leishmanization. We show that immunization with LmCen-/- generated skin CD4+ TRM cells and are supported by the induction of cytokines and chemokines essential for their production and survival similar to leishmanization. Following challenge with wild type L. major, TRM cells specific to L. major were rapidly recruited and proliferated at the site of infection in the immunized mice. Further, upon challenge, CD4+ TRM cells induce higher levels of IFN and Granzyme B in the immunized and leishmanized mice than non-immunized mice. Taken together, our studies demonstrate that the genetically modified live attenuated LmCen-/- vaccine generates functional CD4+ skin TRM cells, similar to leishmanization, that may play a crucial role in host protection along with effector T cells as shown in our previous study.